Fluorescent and Biocompatible Ruthenium‐Coordinated Oligo(p‐phenylenevinylene) Nanocatalysts for Transfer Hydrogenation in the Mitochondria of Living Cells. Issue 20 (13th March 2020) - Dai, Nan; Zhao, Hao; Qi, Ruilian; Chen, Yanyan; Lv, Fengting; Liu, Libing; Wang, Shu
Abstract: It is challenging to design metal catalysts for in situ transformation of endogenous biomolecules with good performance inside living cells. Herein, we report a multifunctional metal catalyst, ruthenium‐coordinated oligo( p‐ phenylenevinylene) (OPV‐Ru), for intracellular catalysis of transfer hydrogenation of nicotinamide adenine dinucleotide (NAD + ) to its reduced format (NADH). Owing to its amphiphilic characteristic, OPV‐Ru possesses good self‐assembly capability in water to form nanoparticles through hydrophobic interaction and π–π stacking, and numerous positive charges on the surface of nanoparticles displayed a strong electrostatic interaction with negatively charged substrate molecules, creating a local microenvironment for enhancing the catalysis efficiency in comparison to dispersed catalytic center molecule (TOF value was enhanced by about 15 fold). OPV‐Ru could selectively accumulate in the mitochondria of living cells. Benefiting from its inherent fluorescence, the dynamic distribution in cells and uptake behavior of OPV‐Ru could be visualized under fluorescence microscopy. This work represents the first demonstration of a multifunctional organometallic complex catalyzing natural hydrogenation transformation in specific subcellular compartments of living cells with excellent performance, fluorescent imaging ability, specific mitochondria targeting and good chemoselectivity with high catalysis efficiency. Abstract : A multifunctional metal catalyst, ruthenium‐coordinated oligo( p‐ phenylenevinylene) (OPV‐Ru) was developed for intracellular catalysis of a transfer hydrogenation reaction. OPV‐Ru self‐assembles into nanoparticles and subsequently works perfectly inside living cells with excellent performance, fluorescent imaging ability, specific mitochondria targeting and good chemoselectivity with high catalysis efficiency (see figure).